Pengaruh Tingkat Pendidikan, Pemahaman Akuntansi, dan Kualitas Sumber Daya Manusia terhadap Penyusunan Laporan Keuangan di UMKM - Naomi Lennesia Lontaan; Fina Ratnasari (Jurnal Mahasiswa Manajemen dan Akuntansi, 2025)
This study aims to determine the relationship between educational level, accounting understanding, and human resource quality affect the financial statement preparation of South Tangerang's culinary MSMEs. A quantitative method was used in which 100 MSME owners were selected using the Slovin formula to represent the target population, and they were asked to complete a Likert scale survey to collect primary data. Data quality evaluation, conventional assumption verification, and hypothesis testing were conducted using IBM SPSS Statistics 29 at the data analysis stage. The results of the study show that MSME owners' educational attainment has little bearing on the preparation of financial accounts. However, it was found that the quality of human resources and accounting understanding had a major influence on the preparation of MSME financial statements. The three distinct factors of education level, accounting understanding, and human resource quality all have a substantial impact on financial statement production at the same time in culinary MSMEs in South Tangerang. This study has significant consequences for initiatives that focus on improving the quality of financial statement production for MSMEs through increased accounting understanding and improved human resource quality.